Odpowiedzi

2009-12-03T19:12:50+01:00
3m + n =9 |×(5)
2m - 5n = -11

15m + 5n=45
2m - 5n=-11

15m+5n+2m+(-5n)=45+(-11)
17m=34|17
m=2


-----------------------
4a - 2 = b
3a + 7b = 1,5

4a-b=2 |× 7
3a+7b=1,5

28a-7b=14
3a+7b=1,5

28a-7b+3a+7b=14+1,5
31a=15,5
a=2


----------------------
5x = 4 - 2y
4x + y = 3


5x+2y=4
4x+y=3 |×(-2)

5x+2y=4
-8x-2y=-6

5x+2y+(-8x)-2y=4+(-6)
-3x=-2 |(-3)
x=2/3


-------------------
6x - 3y = 9
x + 5y = -9,5 |×(-6)

6x-3y=9
-6x-30y=57

6x-3y+(-6x)-30y=9+57
-33y=56
y=-1 i 23/33

1 5 1
Najlepsza Odpowiedź!
2009-12-03T19:33:16+01:00
Pierwszy

3m + n = 9
2m - 5n = -11

n = 9 - 3m
2m - 5n = -11

n=9-3m
2m - 5 (9 - 3m) = -11

n= 9 - 3m
2m - 45 + 15 m = -11

n= 9 - 3m
17m = 34 /: 17

n = 9 - 3m
m = 2

n = 9 - 3*2
m = 2

n = 9 - 6
m = 2

n = 3
m = 2

Drugi

4a - 2 = b
3a + 7b = 1,5

b = 4a - 2
3a + 7 ( 4a - 2 ) = 1,5

b = 4a - 2
3a + 28a - 14 = 1,5

b = 4a - 2
31a = 1,5 + 14

b = 4a - 2
31a = 15,5 /:31

b = 4a - 2
a = 0,5

a= 0,5
b= 4 * 0,5 - 2

a = 0,5
b= 2 - 2

a = 0,5
b = 0

Tzreci

5x = 4 - 2y
4x + y = 3

4x + y = 3
5x = 4 - 2y

y = 3 - 4x
5x = 4 - 2y

y = 3 - 4x
5x = 4 - 2 ( 3 - 4x )

y = 3 - 4x
5x = 4 - 6 + 8x

y = 3 - 4x
5x - 8x = 4 - 6

y = 3 - 4x
3x = - 2 / :3

y = 3 - 4x
x = 2/3 - dwie trzecie - ułamek

x = 2/3
y = 3 - 4 * 2/3

x = 2/3
y = 3 - 8/3

x = 2/3
y = 1/3

Czwarty

6x - 3y = 9
x + 5y = -9,5

6x - 3y = 9
x = -9,5 - 5y

x = -9,5 - 5y
6 ( -9,5 - 5y ) -3y = 9

x = -9,5 - 5y
-57 - 30y - 3y = 9

x = -9,5 - 5y
-33y = 57 + 9

x = -9,5 - 5y
-33y = 66 / : ( -33 )

x = -9,5 - 5y
y = -2

y = -2
x = -9,5 - 5 * ( -2)

y = -2
x = -9,5 + 10

y = -2
x= 0.5

3 4 3